2011
DOI: 10.3945/ajcn.110.000596
|View full text |Cite
|
Sign up to set email alerts
|

Milk protein intake, the metabolic-endocrine response, and growth in infancy: data from a randomized clinical trial

Abstract: HP intake stimulates the IGF-I axis and insulin release in infancy. IGF-I enhances growth during the first 6 mo of life. This trial was registered at clinicaltrials.gov as NCT00338689.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(130 citation statements)
references
References 62 publications
6
116
1
7
Order By: Relevance
“…Accelerated postnatal weight gain can result from high intake of growth-enhancing nutrients such as protein in the infant diet. Available evidence suggests that higher protein intakes increase plasma and tissue levels of insulin-releasing amino acids and of insulin and insulinlike growth factor 1, and thereby increase weight gain and adipogenic activity (36,37) .…”
Section: Accelerated Postnatal Growth Hypothesismentioning
confidence: 99%
“…Accelerated postnatal weight gain can result from high intake of growth-enhancing nutrients such as protein in the infant diet. Available evidence suggests that higher protein intakes increase plasma and tissue levels of insulin-releasing amino acids and of insulin and insulinlike growth factor 1, and thereby increase weight gain and adipogenic activity (36,37) .…”
Section: Accelerated Postnatal Growth Hypothesismentioning
confidence: 99%
“…Several studies observed IGF I levels to positively correlate with current growth parameters and preceding growth velocity in preterm as well as healthy term infants (17)(18)(19)(20). In contrast, findings concerning the correlation between IGF I levels and subsequent growth velocity are inconclusive ( Table 1).…”
Section: The Role Of Igf I In Growth and Body Compositionmentioning
confidence: 55%
“…Socha et al demonstrated that infants fed high-protein followup formula had higher IGF I levels than those fed low-protein follow-up formula (19). Moreover, a minimal caloric as well as a minimal protein intake has to be reached to maintain normal IGF I levels (12).…”
Section: Igf I and Dietary Proteinsmentioning
confidence: 99%
“…Infant nutrition may also programme the hypothalamic-pituitary-adrenal axis. For example, insulin-like growth factor 1 concentrations are lower in breast-fed compared with formula-fed infants (who have more rapid weight gain) and, in a large randomised controlled trial, lower in infants given a standard v. a high protein infant formula (38) . However, whether these effects on insulin-like growth factor 1 persist into adult life, and their impact on development of appetite regulation, obesity (particularly visceral adiposity) and CVD are presently unknown.…”
Section: Endocrine Mechanismsmentioning
confidence: 99%